Analysis of student needs towards the development of scratch games for Arabic vocabulary learning / Muhammad Aiman Zainal Abidin, Fitri Nurul’Ain Nordin and Abdul Azim Mohamad Isa - Zainal Abidin, Muhammad Aiman; Nordin, Fitri Nurul’Ain; Mohamad Isa, Abdul Azim (Universiti Teknologi MARA, Kedah, 2024)
Proficiency in the Arabic language necessitates a mastery of vocabulary. The inability to master vocabulary hinders overall Arabic language proficiency, posing a challenge for numerous students in their learning journey. In contemporary times, technology has become integral across various sectors, including education. The integration of technology is expected to expand the array of teaching and learning methods. Among the modern methods that can be used nowadays is the game-based learning (GBL). Using GBL in the educational process can help facilitate and increase students' interest in engaging in any subjects including language subjects. Therefore, this research will analyze the needs of developing Scratch games to learn the Arabic vocabulary. This research uses mixed method with the aim to identify problems faced by students in learning the vocabulary of Arabic and to identify students' perceptions of the need to develop a Scratch game in learning the Arabic vocabulary. The Development Model of ADDIE (1975) was used in this study as a guide but only at the analysis phase. Respondents in this research are students of the second semester of the Arabic Language Communication Program from the Faculty of the Academy of Language Studies from University Technology MARA (UiTM), Shah Alam. This research uses questionnaire as a way of collecting data and the SPSS statistical package to analyze the data. Based on the findings, the researchers concluded that the need of development of Scratch games for learning Arabic vocabulary should be implemented.